The adoption of market-based practices within care for older people: is the work satisfaction of Nordic care workers at risk? - Teppo Kröger (Nordic Journal of Social Research)
Market-based practices, including privatization and the increased emphasis on managerialism, have entered Nordic social- and health-care systems for elderly people. This article examines whether the adoption of these practices has affected the work satisfaction of care workers in Denmark, Finland, Norway, and Sweden. The data used comes from a postal survey conducted in spring 2005 among Nordic care workers, covering 2716 respondents who provided care for older people. The items analysed include background questions, Likert-scale questions on working conditions, and questions on the presence of different market-based practices in the workplace. The results indicate that there are many variations between the four Nordic countries concerning the adoption of market-inspired practices in the care for elderly people, with Denmark having been the most eager and Norway the least to introduce them. Employees of for-profit employers report a lower level of work satisfaction than public employees. On the other hand, the adoption of most market-based instruments correlates with higher and not lower levels of work satisfaction among care workers working with elderly people.The results do not show a simple connection between the adoption of market-based practices and lower levels of work satisfaction, which might have been expected on the basis of earlier research discussions. However, due to some weaknesses of the data and the many variations between individual market-based models as well as between different Nordic countries, there is cause for caution in the interpretation of the results. It is particularly necessary for policymakers to remain sensitive to the national context.